2016
DOI: 10.1038/srep28135
|View full text |Cite
|
Sign up to set email alerts
|

Body fat mobilization in early lactation influences methane production of dairy cows

Abstract: Long-chain fatty acids mobilized during early lactation of dairy cows are increasingly used as energy substrate at the expense of acetate. As the synthesis of acetate in the rumen is closely linked to methane (CH4) production, we hypothesized that decreased acetate utilization would result in lower ruminal acetate levels and thus CH4 production. Twenty heifers were sampled for blood, rumen fluid and milk, and CH4 production was measured in respiration chambers in week −4, +5, +13 and +42 relative to first part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 49 publications
3
15
0
2
Order By: Relevance
“…Cows calved between October 2014 and April 2015. In wk 5, 13, and 42 (±0.2 wk; SE) of lactation animals were transferred from the freestall into open-circuit respiration chambers as described previously (Bielak et al, 2016). Before the actual gas exchange measure-ments, the animals were adapted several times to the rubber mat-floored chambers to ensure normal feeding and lying behavior.…”
Section: Methane Measurements In Respiration Chambersmentioning
confidence: 99%
See 1 more Smart Citation
“…Cows calved between October 2014 and April 2015. In wk 5, 13, and 42 (±0.2 wk; SE) of lactation animals were transferred from the freestall into open-circuit respiration chambers as described previously (Bielak et al, 2016). Before the actual gas exchange measure-ments, the animals were adapted several times to the rubber mat-floored chambers to ensure normal feeding and lying behavior.…”
Section: Methane Measurements In Respiration Chambersmentioning
confidence: 99%
“…It has been suggested that early life may represent a window during which the establishing rumen microbiome can be manipulated with long-term effects (Yáñez-Ruiz et al, 2015;Abecia et al, 2014). However, CH 4 emissions vary during different periods of an animal's lifetime; for example, CH 4 levels have been reported to increase by up to 35% from early to late lactation (Bielak et al, 2016;Garnsworthy et al, 2012), but this increase is primarily due to an increase in DMI, the main driver of the CH 4 production. Targeting specific periods of increased CH 4 production may facilitate the development of short-term interventions that can contribute to an overall strategy for the mitigation of CH 4 levels from agriculture.…”
mentioning
confidence: 99%
“…Kandel et al (2017) and Chagunda et al (2009a) confirmed such unfavorable associations between CH 4 emissions and milk yield in cattle. Interestingly, the CH 4 eructation traits represent larger CH 4 emissions than the respiration traits (Blaxter and Joyce, 1963), but only the respiration CH 4 traits CH 4 r and CH 4 rmax significantly influenced LBW and EBW. An explanation for the significant impact of "low-level CH 4 " (CH 4 r , CH 4 rmax ) on LBW and EBW might be due to the short recording interval of only 3 min.…”
Section: Phenotypic Impact Of Ch 4 Traits On Lamb Body Weight and Ewementioning
confidence: 96%
“…Consequently, we suggest selection strategies on low CH 4 emissions, in order to avoid further energy losses. Bielak et al (2016) suggested plasma levels of nonesterified fatty acids (NEFAs) as indicators for body fat mobilization. In lactating dairy cows, Bielak et al (2016) identified a negative relationship between CH 4 production per DMI and NEFA plasma levels.…”
Section: Phenotypic Impact Of Ch 4 Traits On Lamb Body Weight and Ewementioning
confidence: 99%
See 1 more Smart Citation